Metabolic reprograming and cancer resistance : an investigation into the metabolic control of cancer-associated fibroblasts on breast cancer cell survival and metastasis - Mitchell, Megan Irvette (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.